Perancangan Sistem Informasi Pengadaan Barang Berbasis Web Menggunakan Metode Waterfall pada PT Global Jaya Elektronik - Aswangga Rakhi Prawira; Farizi Ilham; Ayoga Ugi Diasaputra; Rizqi Muhammad Ikhsan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
This study aims to design and implement a web-based procurement information system at PT Global Jaya Elektronik to improve administrative efficiency, accelerate submission and approval processes, and reduce data entry errors. Existing problems include delayed approval processes, non-real-time monitoring, and the absence of an automatic notification system. The system is developed using the Software Development Life Cycle (SDLC) Waterfall model, consisting of requirements analysis, system design, implementation, and testing. The technology used includes PHP Laravel framework and MySQL database. The results show that the developed system improves procurement efficiency, provides real-time monitoring, and supports faster and more accurate decision-making.